REQUEST STRATEGIES IN LITTLE BIG SHOTS UK - Triyani Tami; Ambalegin Ambalegin (Musamus Journal of Language and Literature, 2020)
This study examined the speech act of request appeared in a television show, Little Big Shots UK. It was a descriptive qualitative study, which the data were utterances in the form of sentences, clauses or words in Little Big Shots UK. The data were collected through the observation and non-participatory technique and analyzed by using the pragmatic identity analysis. The objective of this study was to find out the types of request strategies applied by the speakers in the Little Big Shots UK using the theory of Trosborg (1995). From the collected data, researcher found 37 data of requesting speech act, which 13 (35,1%) data categorized as direct request (2 data using necessity/obligation strategy; 2 data using performative strategy; and 9 data using imperative strategy), 12 (32,4%) data categorized as hearer-oriented condition (8 data using ability/willingness strategy; 4 using suggestory formulae strategy), 11 (29,7%) data categorized as speaker-based condition (9 data using wishes/desire strategy; 2 data using needs/demands strategy), and 1 (2,7%) data categorized as indirect (mild hint strategy). Keywords: directive speech act; request strategy; speech act